A Future with Quantum Machine Learning. - DeBenedictis, Erik P. (Computer (00189162), 2018)
Could combining quantum computing and machine learning with Moore’s law produce a true “rebooted computer”? This article posits that a three-technology hybrid-computing approach might yield sufficiently improved answers to a broad class of problems such that energy efficiency will no longer be the dominant concern.